Pemahaman Masyarakat Karo terhadap Rires Sebagai Pengetahuan Tradisional di Desa Laumeciho - Sari Sesilia Depari; Bella Natasiya; Febiola Br Sembiring; Reh Bungana Perangin-angin; Parlaungan Gabriel Siahaan (Tarbiatuna: Journal of Islamic Education Studies, 2024)
Traditional knowledge, as the core of this research, refers to cultural heritage in the form of systems of knowledge, creativity and innovation that have been passed down from one generation to the next in the Karo tribal community. This research examines the traditional knowledge of the Karo tribal community regarding rieres (lemang) food in Laumeciho Village, as well as how this knowledge is passed down from generation to generation and how social, economic and environmental changes influence the understanding and practice of this traditional knowledge. The research method used is descriptive qualitative research with data collection techniques through interviews, observation and documentation. It is hoped that the results of this research will provide a deeper understanding of the role of rieres food in the culture and identity of the Karo people as well as contribute to the preservation of culture and traditional knowledge in various communities throughout the world. The resource persons in this research were the Karo community at the research location which was conducted in Laumeciho Village, Tanah Pinem District.